The Role of Satisfaction in Mediating Self-Service Technology (SST) on Customer Loyalty - Izzatunnisa’ Habiba Shalsabila; Rini Safitri (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
Economic growth refers to the gradual improvement of a region's ability to produce products and services over a certain period of time. Attaining a substantial increase in economic output undeniably demonstrates the effective advancement of economic development. This study seeks to determine the influence of Regional Investment and Expenditures on the Economic Growth of West Java Province. The inquiry utilized a descriptive methodology. The data was obtained from the Central Statistics Agency Report spanning the years 2015 to 2021. The data analysis technique use the Multiple Linear Regression equation. The research results suggest that both investment and regional expenditure have a substantial influence on economic growth.